Knowledge engineering and computer modelling in CAD : proceedings of CAD86, the seventh International Conference on the Computer as a Design Tool, London, 2-5 September 1986, organized by the journal Computer-Aided Design - Smith, Alison (Butterworths, 1986)
Knowledge Engineering and Computer Modelling in CAD covers the proceedings of CAD86, The Seventh International Conference on the Computer as a Design Tool. The book presents 49 papers that are organized into 14 parts according to their respective themes. The main themes of the conference are modeling and expert systems. Materials covering database, control, and geometric modeling are also presented. The coverage of the text includes expert systems in process planning; selections and evaluation of cost-effective CAD systems; and designing complex artifacts with the assistance of a microcomputer.